EFFECTIVENESS OF VENETOСLAX IN THE TREATMENT OF CHRONIC LYMPHOCYTIC LEUKEMIA (LITERATURE REVIEW) - V. V. Strugov; E. A. Stadnik; A. Yu. Zaritskey (Онкогематология, 2018)
Currently we are facing a revolution in therapy of chronic lymphocytic leukemia, related to the development of novel target drugs, which have markedly improved treatment results in all groups of patients. While inhibitors of Bruton’s tyrosine kinase (ibrutinib, acalabrutinib etc.) and phosphatidylinositol-3 kinase isoforms (idelalisib, umbralisib etc.) are currently in the spotlight, much less attention is paid to antiapoptotic protein inhibitors such as venetoclax. In this review we summarize the results of venetoclax clinical studies in CLL as monotherapy and in combinations. The drug is distinguished by a high rate of complete responses and minimal residual disease eradication in high risk CLL patients, as well as a favorable toxicity profile. This makes it an ideal component of non-genotoxic regimens, aimed at the cure of the disease.